Serial electrocardiographic changes in patients with idiopathic dilated cardiomyopathy - Anil Kumar Choudhary; Ajay Bahl; Yash Paul Sharma; Saurabh Mehrotra; Himanshu Gupta; Somyata Somendra (Indian Heart Journal)
Broad QRS and bundle-branch blocks are associated with poor outcomes in patients with DCM, however, studies on changes in QRS duration and morphology over long-term are limited. We retrospectively analyzed changes in ventricular activation and AV conduction in serial ECGs of 165 DCM patients with a follow-up of at least 5 years from 2003 to 2022. The mean QRS duration at the last follow-up was 114.2 ± 29 vs 106.2 ± 25.3 msec at the baseline(p < 0.0001). Individuals who showed ≥10msec increase in QRS duration also had a higher prevalence of ventricular conduction defects (68%). 13.8% of patients developed broadening of QRS, with an LBBB pattern in over 50%.